Salticid spider phylogeny revisited, with the discovery of a large Australasian clade (Araneae: Salticidae) - Maddison, Wayne P.; Bodner, Melissa R.; Needham, Karen M. (Zootaxa, 2008)
DNA sequence data from four gene regions (28S, 18S, 16S-ND1, and CO1) were gathered from 65 jumping spider (salticid) taxa to supplement previously gathered molecular data for the family's phylogeny. The additional taxa are mostly from Australasia and other regions of the Old World. Bayesian and parsimony analyses support a clade, here called the Astioida, representing a large proportion of the Australasian fauna. Included in the Astioida are, for example, the robustbodied Simaetha and Mopsus, the flattened bark-dweller Holoplatys, the delicate foliage-dweller Tauala, the antlike Myrmarachne and the litter-dwelling Neon. One astioid, Rhondes neocaledonicus, is returned to that genus from its placement in Hasarius. Another newly supported clade, the Aelurilloida, includes the aelurillines, the freyines, and the Bacelarella group of genera. Other newly delimited clades are the Philaeus group (Philaeus, Mogrus, Carrhotus and others), the Leptorchesteae (Leporchestes, Yllenus and Paramarpissa) and the Hasarieae (Hasarius, Habrocestum and Chinattus). These results concur with previous discoveries (e.g., Amycoida, Marpissoida) in suggesting that salticid clades are largely restricted to continental regions.